Driver Filter Design for Software-implemented Loudspeaker Crossovers - YAO, Shu-Nung (Archives of Acoustics, 2014)
A hybrid method is presented for the integration of low-, mid- and high-frequency driver filters in loudspeaker crossovers. The Pascal matrix is exploited to calculate denominators; the locations of minimum values in frequency magnitude responses are associated with the forms of numerators; the maximum values are used to compute gain factors. The forms of the resulting filters are based on the physical meanings of low-pass, band-pass, and high-pass filters, an intuitive idea which is easy to be understood. Moreover, each coefficient is believed to be simply calculated, an advantage which keeps the software-implemented crossover running smoothly even if crossover frequencies are being changed in real time. Instead of designing separate structures for a low-, mid- and high-frequency driver filter, by using the proposed techniques we can implement one structure which merges three types of digital filters. Not only does the integration architecture operate with low computation cost, but its size is also compact. Design examples are included to illustrate the effectiveness of the presented methodology.